Risk disclosures in U.S. non-financial companies’ annual reports: Comparisons among three different industries - Zhang, Jie (2009)
Prior researches on listed companies have reported many useful literatures about risk disclosures either in UK or in other countries. Using the combination of hand-collected data and secondary data, the purpose of this dissertation is to examine risk disclosure practices of fifteen U.S. listed companies from three different industries, over a period of five years. The method of collecting data is content analysis. This study attempts to investigate risk disclosures from the industry point of view, whether there is any relationships between company size, level of company risk, company performance and the volume of risk disclosures. Nine risk measures are used in the hypothesis tests: Turnover ratio, Market Value, Market Capitalization, Gearing ratio, Beta factor, and Book to Market value of equity, Profit margin, Dividend per Share, and Return on Equity. In addition, the developing trend on the volume of risk disclosures and the impacts generated from industry nature to the volume of risk disclosures are also discussed in this study.